PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PENGUNJUNG DI MAL PELAYANAN PUBLIK KANTOR DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN BARRU - Herlinda Herlinda; Zainal Ruma; Burhanuddin Burhanuddin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine how the influence of Service Mall at the Office of the One Stop Integrated Service Investment Service (DPMPTSP) of Barru Regency. The population in this study were visitors to the Public Service Mall at the One-Stop Integrated Service Investment Service Office (DPMPTSP) of Barru Regency and the sample used was 60 visitors using the saturated sample formula. Data was collected using observation and questionnaire methods. The data analysis technique used is simple linear regression analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that service quality has a positive and significant influence on visitor satisfaction at the Public Service Mall at the One Stop Integrated Service Investment Office (DPMPTSP) of Barru Regency.